Diabetes Self-Management Education and Support to Improve Outcomes for Children and Young Adults With Type 1 Diabetes: An Umbrella Review of Systematic Reviews. Issue 5 (October 2021) - Rohilla, Latika; Kaur, Sukhpal; Duggal, Mona; Malhi, Prahbhjot; Bharti, Bhavneet; Dayal, Devi
Purpose: The objectives of this umbrella review were to describe various aspects of diabetes self-management education and support (DSMES)-related interventions and their effect on clinical, behavioral, and psychosocial outcomes among children and young adults with type 1 diabetes (T1DM) and identify gaps in current DSMES-related research. Methods: An umbrella review of systematic reviews on DSMES interventions was conducted in accordance with the PRISMA 2009 statement. Four international medical databases were searched for eligible review articles published in English in the last 10 years that dealt with children and youths with T1DM and were conducted in accordance with a priori protocol. Results: Out of the 234 citations screened, only 8 systematic reviews representing 166 studies were considered eligible for further analysis. Glycemic management (A1C) is the most common outcome variable (108 studies). Common behavioral and psychosocial outcome variables examined are episodes of hypoglycemia (27 studies) and diabetic ketoacidosis (21 studies) and self-care behavior and generic quality of life (20 studies each). Several gaps in DSMES-related research studies are identified, including uneven geographical distribution of study population, methodological weaknesses in study designs, missing important outcome variables, use of nonstandardized assessment tools, and lack of assessment of the sustainability of effects. Conclusion: The effects of DSMES interventions on clinical, behavioral, and psychosocial outcomes are varied. The heterogeneity of implementation and evaluation makes it difficult to draw clear conclusions about elements of DSMES that are most effective. There is a need for long-term assessment of the psychosocial and behavioral outcomes using validated and generalizable instruments.